Comparing Master Recession Curves using Seven Baseflow Recession Models - Latuamury, Bokiraiya (Indonesian Journal of Geography, 2024)
Baseflow recession analysis is an effective method for understanding catchment area releasing flow during dry season (without rainfall), thereby facilitating the management of water resources. Despite the availability of several theories on recession curves, there are limited studies on the comparison of different approaches. To overcome the limitation, several studies have reported the ability of master recession curves (MRC) modeling to combine automated methods for analyzing recession periods and curves shapes based on river flow data. Therefore, this study aimed to compare seven baseflow recession models for MRC characterization in small island watersheds. The Turkey test results showed that MRC visualization varied, particularly in terms of slope parameters and shapes. The seven recession models were grouped into two subsets based on their similarity. The first subsets consisted of Turbulent, Dupuit-Boussinesq aquifer storage, Depression-detention storage, Horton double exponential, Linear reservoir, and Exponential reservoir. Meanwhile, the second subset comprised Hyperbolic reservoir, Turbulent, Dupuit-Boussinesq aquifer storage, Depression-detention storage, Horton double exponential, and Linear reservoir. The findings also showed that the variability of MRC behavior depended on groundwater recharge, storage channel conditions, aquifer characteristics, and climate in the study area. These findings were also relevant to the development of MRC in other regions, such as hydrorecession tools, MRCPtool applications, sensitivity analysis-based Automatic parameter calibration of the VIC model for streamflow simulation over China, and spatial and temporal patterns in baseflow recession in the continental United States.